The Occurrence of Forest Plants in the Desert Mountains of Mongolia and Their Bearing on the History of the Climate - Jäger, Eckehart Johannes (DigitalCommons@University of Nebraska - Lincoln, 2005)
The isolated occurrences of forest plants in the desert mountains of southern Mongolia raise questions as to the mode of their dispersal and the age and direction of former range connections. For species without a possibility of long distance dispersal, a once continuous distribution over the southern Mongolian mountain chains must be assumed. To the Gurvan Saykhan mountains, the forest plants immigrated from the west. Nevertheless their distribution types are eastern Asiatic, or else Eurasiatic with an eastern center of gravity. This shows that the seasonal type of the recent climate with summer rains in eastern Asia influences vegetation composition. The climatic conditions at the time of continuous distribution should include a precipitation sum about 200–300 mm higher than today, as can be judged from the climatic envelope of the recent distribution of these forest plants. This deviates very much from the ’Atlas of paleoclimates,’ but it is corroborated by radiocarbon-dated macrofossils of Picea, Pinus sibirica and Abies found by Russian authors in middle holocene deposits in the Gobi Altay. Between 4,000 and 3,500 yr BP, when the dark taiga forests disappeared due to the aridization in southern Mongolia, also the forest plants in the Gurvan Saykhan became isolated.